Legal Preservation for Ship Crew members based on National and International Law (Case Study: Dalian Ocean Fishing Crew) - Irsyad Zamhier Tuahuns (International Journal Reglement & Society (IJRS), 2020)
Crew members are workers on the ship, in their duties and functions in operating and controlling cargo loads in their duties often get a lot of difficulties and which can result in several problems. Such as physical violence, sexual violence so that it can result in many violations that lead to human rights violations. The presence of crew members in the middle of the sea occasionally gets difficulties from the Indonesian government authorities in controlling their work to the safety of the crew members. The research that has been made is aimed at analyzing the protection and rule of law in the scope of national law and international law. This research is very aimed at making a contribution to the State of Indonesia so that it can provide protection in accordance with the provisions of laws that apply nationally and internationally. In international legal conventions, there are various arrangements that should provide legal protection for workers or crew members, which in principle have the context of international legal standards.